ANALISIS PENGGUNAAN FAKTOR-FAKTOR PRODUKSI TERHADAP TINGKAT PRODUKSI KACANG TANAH (STUDI KASUS DI DESA DOPANG KECAMATAN GUNUNG SARI KABUPATEN LOMBOK BARAT) - MADE SUMA WEDASTRA; I DEWA GEDE SUARTHA (Universitas Mahasaraswati K. Mataram, 2024)
This research was carried out in Dopang Village, Gunung Sari District, West Lombok Regency, aiming to analyze the factors that simultaneously influence production and analyze the production factors that most dominantly influence peanut production in Dopang Village. The number of respondents used was 45 people, which was carried out by census, where the entire population was taken as a sample. Data analysis used multiple Cobb-Douglass linear analysis. Multiple linear results are combined with the classical assumption test.The research results show that: 1). Simultaneously the production factors include land area, seeds, fertilizer, pesticides and labor. has a significant effect on the production of peanut farming in. Dopang Village This can be seen from the test results using the Cobb-duoglass production function, obtained F count of 82.228> F table (0.05)= 1.96, or significant (sig = 0.00 < 0.05. 2). partial production factors: land area and use of KCL fertilizer which have a dominant influence on high production. This can be seen from the calculated t value of the land area compared to the T table, namely (5.576> 1.96), and the use of KCL fertilizer, the calculated t is greater than in the T table, namely 6.116> 1.96, but the number of seeds, fertilizers, pesticides, and labor influence the production of peanut farming in Dopang Village, Gunung Sari District, West Lombok Regency but are not significant. From the research results, it can be suggested: 1). Farmers can still increase their peanut farming production by expanding the planting area, 2). Farmers can still add KCL fertilizer because its use is still lower than what is recommended.